Exploring the Benefit and Sacrifice Factors of Virtual Reality Gameplay - Lee, Chun-Chia; Hsiao, Kuo-Lun; Chen, Chia-Chen (Frontiers in Psychology, 2020)
Although Virtual reality (VR) entertainment is now relatively popular, the adoption of VR devices is still low. In this study, a framework based benefit and sacrifice factors was developed to understand players’ intention to use VR devices to play games. Online questionnaire items were developed and published to collect the responses from university students in Taiwan. The feedback of 152 inexperienced players and 150 experienced players were collected. The eleven hypotheses were tested by using SmartPLS, a structural equation modeling (SEM) tool. The analysis results show that the influences of the benefit factors (flow, spatial presence, and relaxation) on the adoption intention in two groups are consistent. All of the positive influences are supported. Moreover, visual fatigue had the strongest negative effects on flow and intention. Players who are opener to new technology are more possible to adopt VR devices. The findings can provide insights to VR device developers to design their VR devices/contents and marketing strategies.